Intake of dietary fat and fat subtypes and risk of premenstrual syndrome in the Nurses’ Health Study II - Houghton, Serena C. (Br J Nutr, 2017)
Approximately 8–20% of reproductive-aged women experience premenstrual syndrome (PMS), substantially impacting quality of life. Women with PMS are encouraged to reduce fat intake to alleviate symptoms; however, its role in PMS development is unclear. We evaluated the association between dietary fat intake and PMS development among a subset of the prospective Nurses’ Health Study II cohort. We compared 1,257 women reporting clinician-diagnosed PMS, confirmed by premenstrual symptom questionnaire and 2,463 matched controls with no or minimal premenstrual symptoms. Intakes of total fat, subtypes, and fatty acids were assessed via food frequency questionnaires. After adjustment for age, body mass index, smoking, calcium, and other factors, intakes of total fat, monounsaturated, polyunsaturated, and trans fat measured 2–4 years before were not associated with PMS. High saturated fat intake was associated with lower PMS risk (relative risk [RR] quintile 5 [median = 28.1 g/day] versus quintile 1 [median = 15.1 g/day] = 0.75; 95% confidence interval [CI] = 0.58, 0.98; p-trend = 0.07). This association was largely attributable to stearic acid intake, with women in the highest quintile (median = 7.4 g/day) having a RR of 0.75 versus those with the lowest intake (median = 3.7 g/day) (95% CI = 0.57, 0.97; p-trend = 0.03). Individual polyunsaturated and monounsaturated fats, including omega-3 fatty acids, were not associated with risk. Overall, fat intake was not associated with higher PMS risk. High intake of stearic acid may be associated with a lower risk of developing PMS. Additional prospective research is needed to confirm this finding.